Pengaruh Kompensasi dan Tunjangan terhadap Kepuasan Kerja Karyawan - Jusniwati Zai; Romana Rindra Nazara; Fajarman Lahagu; Irwan Nopian Sinaga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of compensation and benefits on employee job satisfaction. Fair, adequate, and transparent compensation is considered a crucial factor influencing employee morale, loyalty, and retention. The study identifies seven key indicators to measure the impact of compensation on job satisfaction: salary adequacy, compensation fairness, punctuality of payments, compensation system transparency, incentives and bonuses, overall compensation satisfaction, and employee retention. The analysis results show that compensation has a significant influence on job satisfaction. Additionally, compensation effectiveness is affected by economic conditions, compensation system structure, and the relevance of compensation to employee needs. The study concludes that well-designed compensation can be a strategic tool for improving performance and reducing employee turnover.